Pengaruh Pelatihan Kerja, Pengalaman Kerja, Dan Motivasi Kerja Terhadap Kinerja Karyawan PT RVS - Aprilia, Nabilah; Iryanti, Endang (Jurnal Riset Pendidikan Ekonomi, 2025)
The progress of a company is strongly determined by the maximum performance of its employees, optimal productivity levels, and the quality of reliable human resources. This research aims to evaluate the extent to which job training, work experience, and work motivation contribute to the improvement of employee performance. This study involved all employees, totaling 55 people at PT RVS, as research subjects, applying a saturated sampling technique in selecting respondents due to the relatively small population size. The approach used in this study is a quantitative approach with a survey method. Primary data was obtained by distributing questionnaires directly to all participants, using a Likert scale with a range of 1 to 5 for variable measurement. Data analysis technique was performed with software support using the Partial Least Square (PLS) statistical method. The research findings indicate that job training, work experience, and work motivation significantly have a positive contribution to improving employee performance. The implication of this research is to provide practical recommendations to the management of PT RVS to intensify relevant training programs and strengthen the motivation-based incentive system to maintain and continuously enhance work performance.